2017
DOI: 10.1037/pha0000119
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent chronic restraint stress (aCRS) elicits robust depressive-like behavior in freely cycling, adult female rats without increasing anxiety-like behaviors.

Abstract: Stress during times of rapid development is a risk factor for Major Depressive Disorder, a mood disorder that disproportionately affects women. We developed an adolescent chronic restraint stress (aCRS) protocol using female rats to address the impact of adolescent stress on female adult depressive-like behavior. Animals were divided into 4 treatment groups: not restrained:saline (NRSAL), not restrained:desipramine (NRDES), restrained:saline (RSAL), and restrained:desipramine (RDES). NRSAL and NRDES rats were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Our study has four main limitations. First, only young adult male rats were used in this study, although CRS has been shown to successfully induce depression-like behaviors in freely cycling adolescent female rats ( Hibicke et al, 2017a , b ). Future studies could expand the applicability of present results by investigating brain changes following CRS in female rats and in older rats.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has four main limitations. First, only young adult male rats were used in this study, although CRS has been shown to successfully induce depression-like behaviors in freely cycling adolescent female rats ( Hibicke et al, 2017a , b ). Future studies could expand the applicability of present results by investigating brain changes following CRS in female rats and in older rats.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, the use of indels will allow us to uncover every gene associated with growth. It could then be combined with the traditional methods of singlestrand conformation polymorphism (SSCP), restriction fragment length polymorphism (RFLP), and amplificationcreated restriction site (ACRS), as well as new methods such as whole-genome resequencing (WGR) and genome-wide association study (GWAS; Tian et al, 2008;Niu et al, 2017;Hibicke et al, 2017;Choi et al, 2015;Jiang et al, 2016). Comparatively analyzing the value of molecular markers should be an important choice.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has four main limitations. Firstly, only male rats were used in this study, even though CRS has been shown to successfully induce depression-like behaviours in freely cycling adolescent female rats (Hibicke et al, 2017a;Hibicke et al, 2017b). Future studies could expand the applicability of present results by investigating brain changes following CRS in female rats.…”
Section: Study Limitationsmentioning
confidence: 99%